2020
DOI: 10.1038/s41598-020-66377-z
|View full text |Cite
|
Sign up to set email alerts
|

Human ZKSCAN3 and Drosophila M1BP are functionally homologous transcription factors in autophagy regulation

Abstract: Autophagy is an essential cellular process that maintains homeostasis by recycling damaged organelles and nutrients during development and cellular stress. ZKSCAN3 is the sole identified master transcriptional repressor of autophagy in human cell lines. How ZKSCAN3 achieves autophagy repression at the mechanistic or organismal level however still remains to be elucidated. Furthermore, Zkscan3 knockout mice display no discernable autophagy-related phenotypes, suggesting that there may be substantial differences… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 56 publications
(84 reference statements)
0
11
0
Order By: Relevance
“…We also identified a role for M1BP, a transcription factor that associates with thousands of genes in somatic cells ( Li and Gilmour 2013 ; Zouaz et al 2017 ; Barthez et al 2020 ). Similarly, CG30020 is also likely to be transcription factor, as in vitro studies have shown that it binds a unique DNA consensus sequence ( Krystel and Ayyanathan 2013 ).…”
Section: Resultsmentioning
confidence: 97%
“…We also identified a role for M1BP, a transcription factor that associates with thousands of genes in somatic cells ( Li and Gilmour 2013 ; Zouaz et al 2017 ; Barthez et al 2020 ). Similarly, CG30020 is also likely to be transcription factor, as in vitro studies have shown that it binds a unique DNA consensus sequence ( Krystel and Ayyanathan 2013 ).…”
Section: Resultsmentioning
confidence: 97%
“…Methylation in promoter regions of ZSCAN31 in the brain had an effect on schizophrenia ( Pineda-Cirera et al, 2022 ). ZKSCAN3 plays a role in the transcriptional regulation of autophagy ( Pan et al, 2017 ; Barthez et al, 2020 ; Cho et al, 2021 ). Autophagy is an important cellular process that maintains homeostasis by recycling damaged organelles and nutrients during cell development and stress.…”
Section: Resultsmentioning
confidence: 99%
“…Autophagy dysfunction in the hippocampus, especially in the CA2 region, may relate to deficits of social communication and interaction in schizophrenia patients ( Yang and Xu, 2020 ). Gene expression pattern of ZNF391 in the brain led to the three biotypes, which performed significantly differently in working memory and demonstrated different gray matter volumes in the right inferior frontal orbital gyrus ( Barthez et al, 2020 ). These data provide clues for further exploring the pathogenesis and cognitive impairment mechanism of schizophrenia.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, more and more ZNFs were identified as oncogene and promoted various tumors via enhancing cell proliferation [24], promoting cell migration and invasion [25], suppressing autophagy [26], and epithelial-mesenchymal transition [27]. ZNF460 gene co-expression network analysis established that ZNF460 had a positive correlation with ZNF484, ZNF121, HMBOX1 and a negative correlation with MGAT4B, UCHL3, GTF2IRD1.…”
Section: Discussionmentioning
confidence: 99%